2017
DOI: 10.1186/s12966-017-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of behaviour change interventions to reduce population salt intake

Abstract: BackgroundExcess salt intake is a major cause of raised blood pressure—the leading risk factor for death and disability worldwide. Although behaviour change interventions such as awareness campaigns and health education programs are implemented to reduce salt intake, their effectiveness is unclear. This global systematic review investigates the impact of population-level behaviour change interventions that aim to reduce salt intake.MethodsA search for published and grey literature was conducted using PubMed, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 42 publications
(175 reference statements)
6
67
0
Order By: Relevance
“…These behaviour-change interventions have been important, particularly as there was no previous public education about salt reduction and salt added by the consumer during cooking or eating is still a major source of salt in the Samoan diet. Although they have likely led to some of the improvements in salt-related knowledge and behaviours, previous reviews suggest these interventions alone are unlikely to have a substantial impact on population salt intake [ 19 , 38 ]. Complementary structural interventions that create a healthier food supply and environments that support lower salt intake such as reformulation to reduce salt content in foods, fiscal, trade or healthy food procurement policies are needed to ensure a substantial and sustained impact [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These behaviour-change interventions have been important, particularly as there was no previous public education about salt reduction and salt added by the consumer during cooking or eating is still a major source of salt in the Samoan diet. Although they have likely led to some of the improvements in salt-related knowledge and behaviours, previous reviews suggest these interventions alone are unlikely to have a substantial impact on population salt intake [ 19 , 38 ]. Complementary structural interventions that create a healthier food supply and environments that support lower salt intake such as reformulation to reduce salt content in foods, fiscal, trade or healthy food procurement policies are needed to ensure a substantial and sustained impact [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same people were interviewed in 2014 and 2015 thus resulting in potential reporter bias because of social desirability as reported in the literature [ 25 ]. The lack of a control group is a major limitation to the study design but could not be included because of the population level intervention strategy which necessitated a pre-post quasi experimental study design.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that mass media campaigns may be an effective tool that can make an important contribution to strategies to reduce the consumption of discretionary salt intake among the South African population. Trieu and colleagues [ 25 ] in a recent review concluded that education or awareness campaigns alone are unlikely to be adequate to achieve the WHO target of a 30% reduction in average salt intake. We agree that multi-pronged strategies using multiple channels of communication need to accompany the salt reduction regulations of certain foods stuffs.…”
Section: Discussionmentioning
confidence: 99%
“…The key health consequence of a high dietary salt intake is high blood pressure [9,10] and Australia has committed to reducing the average salt intake by 30% by 2025, as per World Health Organization (WHO) recommendations [11]. Currently salt reduction strategies are being implemented in various countries to support individuals reducing their sodium intake [12,13]. However, potassium intake is often not a focus of these strategies; and therefore a missed opportunity to improve health.…”
Section: Introductionmentioning
confidence: 99%